2013
DOI: 10.1021/la4000473
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Structural Description of Calcium–Sodium Aluminosilicate Hydrate Gels: The Cross-Linked Substituted Tobermorite Model

Abstract: Structural models for the primary strength and durability-giving reaction product in modern cements, a calcium (alumino)silicate hydrate gel, have previously been based solely on noncrosslinked tobermorite structures. However, recent experimental studies of laboratory-synthesized and alkali-activated slag (AAS) binders have indicated that the calcium-sodium aluminosilicate hydrate (C-(N)-A-S-H) gel formed in these systems can be significantly crosslinked. Here, we propose a model that describes the C-(N)-A-S-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
265
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 443 publications
(299 citation statements)
references
References 56 publications
34
265
0
Order By: Relevance
“…Many papers can now be found in the literature that confirm the presence of Q 3 (nAl) units in the C-A-S-H gels forming during slag alkaline activation (53,63,69,70). One prominent article, authored by Puertas et al (69), reported that in C-A-S-H gels forming in slag activated with a NaOH solution, the existence of tetrahedral Al in bridging positions in the silicate chains goes hand-in-hand with a considerable increase in the number of Q 2 (1Al) units, as well as with a small amount of Q 3 (nAl) units.…”
Section: Fundamentals Of Alkaline Activation In Calcium-rich Systems:mentioning
confidence: 91%
See 1 more Smart Citation
“…Many papers can now be found in the literature that confirm the presence of Q 3 (nAl) units in the C-A-S-H gels forming during slag alkaline activation (53,63,69,70). One prominent article, authored by Puertas et al (69), reported that in C-A-S-H gels forming in slag activated with a NaOH solution, the existence of tetrahedral Al in bridging positions in the silicate chains goes hand-in-hand with a considerable increase in the number of Q 2 (1Al) units, as well as with a small amount of Q 3 (nAl) units.…”
Section: Fundamentals Of Alkaline Activation In Calcium-rich Systems:mentioning
confidence: 91%
“…This gel was also observed to contain a small amount of alkalis (normally Na), that neutralised the charge imbalance created when a Si is replaced by an Al tetrahedron. Actually, then, these are calcium-sodium aluminosilicate hydrate [C-(N)-A-S-H] gels (70)(71)(72)(73) proposed a model to describe this gel as a mix of cross-linked and non-cross-linked tobermorite-based structures (the cross-linked substituted tobermorite model, CSTM).…”
Section: Fundamentals Of Alkaline Activation In Calcium-rich Systems:mentioning
confidence: 99%
“…Al substitutes into bridging sites with strong preference over paired sites in these chains [15,16]. It has also been suggested that the aluminosilicate chains in C-(A-)S-H products can cross-link in lowCa (Ca/Si < 1) cements [17] to form disordered analogues of 'double chain' calcium silicate minerals, e.g. 11Å tobermorite [18] ( Figure 1A).…”
Section: Preprint Version Of Accepted Article Please Cite As: Rj Mmentioning
confidence: 99%
“…Samples A and B (empirical formulas 2SiO2·Al2O3 and 4SiO2·Al2O3, respectively) were chosen to represent the range of bulk silicon and aluminium content typically found in fly ashes, with A also representing the approximate composition of metakaolin (see Figure 1) [19]. Samples C, D, E and F (empirical formulas 0.800CaO·SiO2·0.078Al2O3, 1.214CaO·SiO2·0.078Al2O3, 0.709CaO·SiO2·0.026Al2O3 and 1.104CaO·SiO2·0.026Al2O3, respectively) were chosen to enable synthesis of binders exhibiting chemistry in regions of the quaternary CaO -Na2O -Al2O3 -SiO2 system which are important for the study of sodium-and aluminium-substituted calcium silicate hydrate gels, the main reaction product present in alkali-activated slag binders [11,20]. …”
Section: Aluminosilicatesmentioning
confidence: 99%
“…This can be particularly challenging due to the wide variation of chemical and physical characteristics exhibited by commercial geopolymer precursors where a range of chemical reactivity is observed, Postprint of a paper published in Powder Technology, 29(2016): [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Version of record is available at http://dx.doi.org/10.1016/j.powtec.2016.04.006 3 meaning it is often difficult to distinguish reactive from inert species.…”
Section: Introductionmentioning
confidence: 99%